Otimização do código do sistema de navegação e controle de robôs móveis baseado em NMPC para embarcar em arquiteturas de baixo custo - Azevedo , Diego Sousa de (2015)
The purpose of this study is to adapt and embed a navigation system and control of mobile robots, based on NMPC, in a low-cost board existent on the market, to provide sufficient com-putational resources so that the robot is able to converge, without losing performance, using the same horizons applied in a Laptop. The obtained results demonstrate the proposed scenario according with the experiments, proving that it is possible to use low cost boards, to a navigation system and control of mobile robots, based on NMPC, using the same predictive and control horizons applied in a Laptop.